2013
DOI: 10.3390/en6042175
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Hydrogen Production from Pineapple Waste Extract by Anaerobic Mixed Cultures

Abstract: A statistical experimental design was employed to optimize factors that affect the production of hydrogen from the glucose contained in pineapple waste extract by anaerobic mixed cultures. Results from Plackett-Burman design indicated that substrate concentration, initial pH and FeSO 4 concentration had a statistically significant (p ≤ 0.05) influence on the hydrogen production potential (P s ) and the specific hydrogen production rate (SHPR). The path of steepest ascent was undertaken to approach the optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…A maximum xylanase activity of 45.63 U/mL and bio-hydrogen potential of 440 mL H 2 /g VS was observed at pH 5. Similar results are reported by Reungsang and Sreela-or [50] for the maximum hydrogen potential at an initial pH 5.56. The optimum pH 5 for obtaining the maximum rate of H 2 is found same when compared with similar experiments of pH 5-6 using disaccharide sucrose and heat treated inoculum [51].…”
Section: Effect Of Initial Ph On Both Bio-hydrogen and Enzyme Productionsupporting
confidence: 90%
“…A maximum xylanase activity of 45.63 U/mL and bio-hydrogen potential of 440 mL H 2 /g VS was observed at pH 5. Similar results are reported by Reungsang and Sreela-or [50] for the maximum hydrogen potential at an initial pH 5.56. The optimum pH 5 for obtaining the maximum rate of H 2 is found same when compared with similar experiments of pH 5-6 using disaccharide sucrose and heat treated inoculum [51].…”
Section: Effect Of Initial Ph On Both Bio-hydrogen and Enzyme Productionsupporting
confidence: 90%
“…The higher production of short chain organic acids could also be possible at higher substrate concentrations. This could result in a drop of pH to a level that is not suitable for hydrogen production [52]. In the present study, it was found that the final pH of the fermentation broths tended to decrease when higher biomass concentrations were used (data not shown), which correlated with the production of organic acids shown in Figure 2.…”
Section: Methodsmentioning
confidence: 53%
“…Later, it was placed in a preheated oven at 100˝C for 30 min in order to deactivate hydrogenotrophic methanogens [22,23]. The volatile solids, volatile fatty acids, alkalinity and pH of the sludge were 2.87%, 13950 mg/L, 3700 mg/L and 7.1, respectively.…”
Section: Seeded Sludgementioning
confidence: 99%